Implementation of Retrieval Practice After Learning the Immune System in High School: Students' Perceptions and Self-Efficacy - Cahyani, Raditha Putri; Rahmat, Adi; Suwandi, Tri (Jurnal Penelitian dan Pembelajaran IPA, 2024)
Retrieval practice is a learning strategy that has been shown to be effective in improving student learning. However, more research needs to be done on a classroom scale that examines students' perceptions of retrieval practice and its relationship to self-efficacy. The purpose of this study was to examine students' perceptions of retrieval practice and its influence on self-efficacy in the context of immune system learning. The research was conducted with 128 high school students from four 11th-grade science classes who were divided into two groups: two classes as the experimental group and two classes as the control group. Students in both groups underwent classroom learning about the immune system using Discovery Learning. Three days after the classroom learning, students in the experimental group received additional learning in the form of retrieval practice followed by feedback. Meanwhile, two classes of the control group were spent re-reading. Data on self-efficacy and students' perceptions of retrieval practice were collected after three weeks of learning. Differences in self-efficacy data between the experimental and control groups were analyzed using the Independent Samples t-test. The Spearman Rho test was used to determine the relationship between self-efficacy and students' perceptions in the experimental group. Research has shown that retrieval practice has a positive effect on self-efficacy. However, students' perceptions of retrieval practice vary widely, although most students have shown positive perceptions. These perceptions have a significant positive relationship with self-efficacy. Students who perceive retrieval practice positively generally have high self-efficacy. Therefore, students who use retrieval practice tend to have higher self-efficacy than those who do not. The difference was significant. It suggests that students' perceptions of retrieval practice play an essential role in determining the effect of retrieval practice on self-efficacy.